Environmental moisture ingress characteristics in high-voltage cable port assemblies: Temperature-humidity coupling effects analysis - Sichen Qin; Zixin Li; Qian Wang; Bolan Jing; Rui Liu (Results in Engineering)
As the field of storage cables is yet to mature in sealing devices and methods, the ports of such cables are poorly sealed. This causes environmental moisture to intrude from the ports, rendering the cable ports damp. In order to investigate the moisture intrusion characteristics of XLPE cable ends stored in different temperature and humidity environments, this paper carries out water absorption tests of cable materials (XLPE, semi-conductive rubber) under different temperature and humidity conditions. The Langmuir water diffusion model was utilised to derive the microscopic parameters of water absorption diffusion coefficient for various cable materials. The diffusion coefficient function model was established. Multi-physics field simulation software was employed to construct a 110 kV single-core cable end water absorption simulation model. The findings indicate that within a high-temperature and high-humidity environment, the water absorption rate of XLPE and semi-conductive rubber reaches 0.16 % and 0.55 %, respectively. The temperature range under consideration is from 25 to 60 degrees Celsius. The material under investigation is high-humidity XLPE, and the diffusion coefficient of water absorption is increased by approximately 38.8 % and 58.8 %. The single-core cable water absorption simulation model demonstrated that the water diffusion depth at elevated temperatures and humidity levels (25.4 cm) was 12.4 times greater than that at ambient temperatures and low humidity. The infrared spectra show that the characteristic peak intensity of the OH bond in water - absorbing XLPE samples is significant, indicating substantial internal water intrusion. This verifies the accuracy of the water-absorption simulation model.